Support groups for mothers of newborns hospitalized in a neonatal unit - Elysangela Dittz Duarte; Erika da Silva Dittz; Bárbara Christina Noelly e Silva; Ludimila Laranjeiras Barros Rocha (Universidade Federal do Ceará, 2013)
Mothers' stay with their babies at a neonatal intensive care unit requires the development of assistance initiatives that also take their needs into account. Games, leisure and educational activities, as well as support groups, are used to alleviate tensions, share information and foster socialization in hospital institutions. We sought to describe group activities during newborn mothers support and guidance. These mothers were hospitalized in the Neonatal Intensive Care Unit of the Sofia Feldman Hospital in Belo Horizonte/Minas Gerais in 2010. Data was collected from records provided by the institution professionals and the authors' experiences. Support groups offer a discussion and listening environment, allowing the construction of alternatives to face difficulties resulting from hospitalization, thus stimulating maternal participation in child care and enabling the interaction between the mothers and the health care team.